Integrating ecosystem organization, quality and services indicators in the ecological security assessment - Tang, Butian; Wang, Hao; Peng, Lixian; Wang, Zhuangzhuang; Liu, Jiamin; Liwei, Zhang; Jiao, Lei (Land degradation & development, 2023)
Ecological security is a vital component of regional security and significantly influences regional sustainable development. The assessment of ecological security is the cornerstone of relative research to coordinate ecological protection and economic developments. However, a framework that enables systematic assessment of the ecological security still needs further exploration. A framework that includes ecosystem organization ( O ), quality ( Q ), and services ( S ) was proposed to evaluate the ecological security in southeast Qinghai‐Tibet Plateau (QTP) in this study. Results showed that: (1) From 2000 to 2020, ecosystem organization in the study area showed an improving trend, with 61.33% of counties experiencing an increase in O value; (2) The ecosystem quality showed an increasing trend, with the proportion of increased areas amounting to 54.46%, and the significantly increased area occupied 3.38% of the study area; (3) The total trend of ecosystem services decreased, among them, habitat provision and soil conservation both presented an increasing trend, while water yield performed a decreased trend; (4) The ecological security in the southeast of QTP has been improved, which increased in north of the study area and decreased in south part. Overall, our study provided a novel view to characterize the physical status of the natural environment and enriched the methodology of ecological security assessment. More attention should be received by the different roles of ecosystem organization, quality, and services in ecological security in future studies, which is helpful to reflect the current situation and changing trends of regional ecological security more reasonably and comprehensively.